Serum Levels of Selected Inflammatory Markers in Farm Workers Exposed to Organophosphate Pesticides (African Journal of Biomedical Research, 2023)
Despite the acute and chronic adverse effects associated with the use of organophosphate pesticide (OPs), they continue to be used indiscriminately by farm workers. Exposure to various toxicants such as OPs has been shown to evoke various immune responses including inflammatory processes which have been implicated in the aetiology and pathogenesis of several pathological disorders. Although occupational exposure to OPs is linked with dysregulated immune responses, information on the group of farm workers at high risk of dysregulation is lacking. This study therefore, determined the differences in the serum levels ofselected inflammatory markers in farmers and pesticide applicators exposed to OPs. One hundred and eighty adult males comprising 60 pesticide applicators (PA), 60 farmers exposed to OPs for more than 5 years, and 60 apparently healthy adults without occupational exposure to OPs who served as controls were enrolled into this study. Differential leucocyte count was determined using thin film microscopy and Neutrophil-lymphocyte ratio (NLR) was calculated. Serum level of C-reactive protein (CRP) was determined using ELISA and activity of Nicotinamide adenine dinucleotide phosphate (NADPH)oxidase (Nox) was determined spectrophotometrically. The mean serum level of CRP and Nox activity were significantly higher in PA and farmers compared with the controls. In contrast, NLR was significantly lower in PA and farmers compared with the controls. However,the mean serum level of CRP was significantly higher in PA compared with farmers. Long term exposure to OPs is associated with systemic inflammation which is more pronounced in PA. Also, long term exposure to OPs seemed to be associated with heightened phagocytic activities which could promote oxidative injury of the lung.
Keywords: Menopause; Obesity; Nutritional status; Women